Systemic lupus erythematosus: a clinical update. Issue 8 (22nd August 2021) - Connelly, Kathryn; Morand, Eric F.
Abstract: Systemic lupus erythematosus (SLE) is a multi‐system autoimmune disease known for its complexity and heterogeneity. Striking diversity can be observed between individual patients, in terms of clinical manifestations, serological abnormalities, disease progression and response to therapy. Furthermore, dysfunction of a broad range of immune pathways underlies disease development and expression. An appreciation of this diversity is vital in order to diagnose accurately and appropriately treat patients with SLE as there is no one‐size‐fits‐all diagnostic test or treatment. Optimal management involves identifying affected organs, assessing severity, differentiating activity from irreversible damage and tailoring immunosuppressive treatment accordingly. Non‐pharmacological interventions, attention to disease and treatment‐related comorbidities and addressing the significant impact on health‐related quality of life are also crucial to maximising patient outcomes.